Mucolipidosis Type III: A Rare Disease in Differential Diagnosis of Joint Stiffness in Pediatric Rheumatology - Çiğdem Seher KASAPKARA,; Meltem AKÇABOY,; Fehime KARA EROĞLU,; Betül Emine DERİNKUYU, (Archives of Rheumatology, 2018)
Mucolipidoses are metabolic disorders with autosomal recessive inheritance caused by deficiency of N-acetylglucosamine- 1-phosphotransferase leading to accumulation of glycosaminoglycans and sphingolipids intracellularly. The differential diagnosis of mucolipidosis II or III is based on the age of onset, clinical findings and degree of severity. In this article, we present four pediatric patients with mucolipidosis III or pseudo-Hurler polydystrophy who admitted to our hospital with joint stiffness. They were from consanguineous families with characteristic radiographic findings. The joints were painless and the rheumatologic evaluation and inflammation markers were negative. Mucolipidosis is a rare disease in pediatric patients to remember in differential diagnosis of joint stiffness.